Enhancing Mathematics Achievement Through Cooperative Learning: A Study of The Jigsaw Technique in Exponent Multiplication and Division - Kaewrueang, Kwanpichcha; Phobubpa, Ratchadaporn; Haarsa, Panyawat (LPPM Universitas Terbuka, 2025)
Motivating students and fostering deeper conceptual understanding remain key challenges in mathematics education, particularly with abstract topics such as exponent multiplication and division. Achievement gaps often result from traditional lecture-based methods that fail to address diverse learning needs. Cooperative learning strategies, especially the Jigsaw technique, have been shown to improve student engagement, peer interaction, and content mastery. The method promotes active participation, accountability, and deep comprehension through structured group collaboration, making it particularly effective for challenging mathematical concepts. This study investigates the impact of the Jigsaw technique on eighth-grade students’ performance in exponent multiplication and division. A posttest-only experimental design was employed with 30 secondary school students. Data were collected through a researcher-developed posttest containing multiple-choice and short-answer questions aligned with national learning objectives. The data were analyzed using descriptive statistics (mean, percentage, standard deviation) and a one-sample t-test to evaluate statistical significance. The results demonstrated a significant improvement in student performance (M = 15.13, SD = 2.10, t = 8.186, p < .05), surpassing the 60% proficiency benchmark. These findings suggest that the Jigsaw method not only enhances mathematical understanding but also cultivates essential 21st-century skills such as critical thinking, communication, and teamwork.